Cover Jurnal Fitopatologi Vol. 21 No.1 , Maret 2025: Cover Jurnal Fitopatologi Vol. 21 No.1 , Maret 2025 - Editors Jurnal Fitopatologi Indonesia (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2025)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Vol. 21 No.1 , Maret 2025.